STAR-RIS-Assisted Radar-Communication Co-Existence System - Dai, Jianxin; Han, Tuobin; Pan, Cunhua; Wang, Kezhi; Hong, Ren (IEEE Vehicular Technology Conference, 2023)
To combat the half-space coverage and enhance the flexibility of the reconfigurable intelligent surface (RIS) technology, a simultaneously transmitting and reflecting RIS (STAR-RIS) is applied in the radar-communication co-existence (RCC) system, where the signal through STAR-RIS is transmitted to opposite spaces, and STAR-RIS is utilized to handle the interference from the base station (BS) to the radar. A radar detection probability maximization problem by optimizing the transmit beamforming vector of the BS and the transmission-and reflection-coefficient matrices of the STAR-RIS is formulated, subject to the power constraint of the BS and the communication rate constraints of users. The problem is challenging to solve due to the highly coupled variables. We convert it into two sub-problems and propose an efficient alternating optimization (AO) algorithm to solve this non-convex problem. The simulation results validate the convergence of the proposed algorithm and the performance advantages of using STAR-RIS over conventional RIS.